Predicting Death After Thrombectomy in the Treatment of Acute Stroke - Awad, Al-Wala; Kilburg, Craig; Ravindra, Vijay M.; Scoville, Jonathan; Joyce, Evan; Grandhi, Ramesh; Taussky, Philipp (Frontiers in Surgery, 2020)
Introduction: Treatments for acute stroke have significantly improved in the past decade, with emergent thrombectomy emerging as the standard of care. Despite these advancements, death after successful thrombectomy continues to pose a significant problem. Identifying patients least likely to benefit from thrombectomy would for provide improved use of a limited resource and management of patient expectations. Method: We retrospectively reviewed the medical records of patients who underwent emergent thrombectomy of either anterior or posterior circulation strokes between January 2012 and January 2017. Relevant patient clinical data was collected and analyzed in a multivariable regression with a primary outcome of death at 90 days. Results: A total of 134 patients underwent emergent endovascular thrombectomy during the study period; sufficient clinical data was available in 111 of the them. Of these, 42 patients died during the 90-day post-procedural period and 69 patients survived this period. The median NIHSS score at presentation was 14 in surviving patients and 20 in nonsurviving patients (p<0.002). Surviving patients were younger (60.4 ± 17.3 years vs. 66.6 ± 18.3 years, p<0.03) and less likely to have a history of cancer (4.4% vs. 26.2%, p<0.002), achieved higher rates of revascularization (78.3% vs. 50.0%, p<0.003), had a lower rate of hemorrhagic conversion (21.7% vs. 47.6%, p<0.004), and experienced fewer technical complications during their case (7.4% vs. 26.2%, p<0.01). Overall, there were 16 intraprocedural complications and no procedural deaths. Conclusion: As emergent thrombectomy for the treatment of acute stroke becomes more prevalent, appropriate patient selection will be crucial in the utilization of a limited and costly intervention. Death within 90 days after thrombectomy appears to be more prevalent among older patients, those with postprocedural hemorrhage or intraprocedural complications, and those with a history of cancer.